Dementia in prison: ethical and legal implications. Issue 3 (1st June 2002) - Fazel, S; McMillan, J; O'Donnell, I
Abstract : As the number of elderly prisoners increases in the UK and other Western countries, there will be individuals who develop dementia whilst in custody. We present two case vignettes of men with dementia in English prisons, and explore some of the ethical implications that their continuing detention raises. We find little to support their detention in the various purposes of prison put forward by legal philosophers and penologists, and conclude by raising some of the possible implications of The Human Rights Act 1998.